PENGARUH LATIHAN BERLARI ZIG ZAG MELEWATI CONE TERHADAP KETERAMPILAN DRIBBLE PADA SSB PUMA FC U-12 - Aldirus Difedema Fidel; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the problems stated above, the problem can be formulated as follows: Does the ZIG ZAG Running Cone Pass practice affect the SSB Puma Fc U-12 dribble skills. The sample is simply interpreted as part of the population that is the actual data source in a study. According to Hadi (1993: 321)